Enterprise GIS concepts and applications - Woodard, John (GIS professional) (Boca Raton, FL : CRC Press, 2020)
This book defines and discusses how the field of Enterprise Architecture (EA) can be incorporated into the design of Enterprise Geographic Information Systems (EGIS). The objective of EA is to develop a strategic plan that structures an organization's resources (data, information, people, and assets) into one team that works together to achieve the company's objectives in an efficient, agile, and adaptable way. It demonstrates how EA concepts can be incorporated within EGIS by improving the system's efficiency and reliability. Through real-world examples and step-by-step explanations, the reader will reach a comfortable understanding of the theories and methods discussed in the book.
OCLC-licensed vendor bibliographic record.
Keywords: Geographic information systems; Management information systems; Business enterprises -- Computer networks; BUSINESS & ECONOMICS / Management Science; LAW / Environmental; TECHNOLOGY / Environmental Engineering & Technology